The Implementation of Increasing Village Income Through Village-Owned Business Entities - Adri Wontami (Estudiante Law Journal, 2019)
Abstract: The purpose of this study was to determine the increase in village income through village-owned enterprises. The research method used is a normative-empirical legal research dualism where the research uses a normative-empirical legal case study in the form of a product of legal behavior. The approach used is a juridical approach and analytical techniques using qualitative analysis methods. The results of this study indicate that Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises on increasing Village Original Income has not been effective in improving community welfare. The social benefits in implementing this program have not been felt so it is necessary to increase it.Keywords: Improvement; Income; Village Owned Enterprises